Home for half-term - Blyton, Enid (A wishing-chair adventure, 2020)
A magical wishing-chair short story from Enid Blyton with brand new full-colour illustrations! Mollie and Peter are very lucky - they have a wishing-chair that will fly them to any magical land and grant them their wish! And so when they arrive home from school for the half-term holidays, they can't wait to embark on their next adventure!.